A Comparative Study of Education as Soft Power: The Cases of China and the United States - Dr. Muhammad Shahzad Ashfaq (Research Journal of Psychology, 2025)
Education is increasingly used as a diplomatic tool to project soft power globally. This study explores how China and the United States employ education to shape their international image and influence. The study aims to compare educational strategies used by both nations, analyze their effectiveness, and assess international students' perceptions. The target population includes international students currently enrolled in Chinese and U.S. universities. A purposive sample of 20 international students (10 from each country) was selected. Convenience sampling was also used for expert interviews. Data was collected through semi-structured interviews and document analysis, including policy papers and institutional reports. A qualitative comparative case study design was employed, grounded in Nye’s soft power theory and constructivist international relations theory. Interviews were transcribed and coded thematically. Cross-case analysis was conducted to identify similarities and contrasts. Both nations use scholarships and cultural promotion, but the U.S. emphasizes prestige, while China focuses on accessibility and regional ties. Recommendations: Both countries should ensure academic freedom and intercultural engagement to enhance the credibility and sustainability of their soft power strategies.